1987
DOI: 10.1051/jphyscol:1987394
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Propagation Behavior of 2091 T8 and 2024 T3 Under Constant and Variable Amplitude Loading

Abstract: The fatigue crack propagation behavior of the damage tolerant 2091 T8 was compared with that of 2024 T3. Constant amplitude tests were performed in vacuum, air, and NaCl solution at R = 0.175 and in air at R = 0.7. The variable amplitude tests included periodic underloads superimposed on constant amplitude tests at R = 0.7, and periodic overloads in combination with low R-ratio tests. In general it was found that the crack propagation resistance of 2091 was slightly inferior in the lower AK-region as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
3
19
0
Order By: Relevance
“…The Lo-Hi sequence produces an acceleration of crack growth rate, above the steady state level expected for the high block, followed by a gradual reduction to the corresponding steady-state DK 2 level. This behaviour is identical to that generally observed following an underload [27]. The trends illus- [19].…”
Section: Transient Crack Growth Behavioursupporting
confidence: 70%
“…The Lo-Hi sequence produces an acceleration of crack growth rate, above the steady state level expected for the high block, followed by a gradual reduction to the corresponding steady-state DK 2 level. This behaviour is identical to that generally observed following an underload [27]. The trends illus- [19].…”
Section: Transient Crack Growth Behavioursupporting
confidence: 70%
“…2(b) shows clearly that during the stable crack growth rate stage crack growth retardation increases with DK under remotely spaced overloads (n BL R100). Moreover, as observed in similar tests performed by Iwasaki et al [9] in SM50B steel and by Ohrloff et al [10] in 2024-T6 and 2091-T8 aluminium alloys, also in AlMgSi1-T6 aluminium alloy, the crack growth acceleration phenomenon observed under too closely spaced overloads decreases with DK. During this phase, the acceleration phenomenon changes even to crack growth retardation for DK values above approximately 10 MPa m 1/2 .…”
Section: Typical Transient Behaviour and Periodicity Effect Of Singlesupporting
confidence: 67%
“…Initially, a retardation period identical to that induced by a single peak overload [3][4][5] is observed for less frequently applied overloads. For overloads applied each 10 baseline cycles this initial stage is similar to the one generally observed after an underload [10,11]. The subsequent crack growth rate increases in a stable manner.…”
Section: Typical Transient Behaviour and Periodicity Effect Of Singlesupporting
confidence: 56%
See 1 more Smart Citation
“…Skorupa analysed several works (43,(52)(53)(54)(55)(56)(57)(58) that showed that an underload applied after an overload can generate reverse plasticity ahead of the crack tip which partially nullifies the beneficial retardation effect of the overload.…”
Section: Effect Of Applying Underloadsmentioning
confidence: 99%